Pemikiran Ulang Materialitas: Kajian Fenomenologi Pengalaman Penciptaan Seni dari Pelukis Cat Minyak Tradisional di dalam Realitas Virtual - Sidik, Muhamad Fauzan; Damayanti, Nuning Yanti; Mutiaz, Intan Rizky; Grahita, Banung (Fakultas Seni Rupa dan Desain ITB, 2024)
Recent technological developments have brought back virtual reality (VR) as a new creative medium. This research investigates how artists with no prior VR experience perceive and employ immersive VR environments to translate their physical world creative concepts into the virtual realm. By bridging the gap between traditional and virtual reality art, this study contributes to a deeper understanding of affordance theory in today’s context. Using a phenomenological approach, data was collected through immersive VR painting sessions, think-aloud protocols, and reflective interviews. Over three sessions, one selected participant utilized OpenBrush to explore the affordances of VR painting. Key findings reveal a transformative shift in artistic knowledge and practice. Participants adapted their understanding of materials and techniques to the unique affordances of VR, aligning with affordance theory and actor-network theory. The study's implications for artists are that by integrating VR into traditional art practices, artists can explore new creative avenues. Additionally for VR developers, the findings suggest potential improvements to VR tools, such as enhancing haptic feedback or developing more intuitive interfaces to better support artistic expression.